PENGARUH CURRENT RATIO (CR), RETURN ON ASSET (ROA), PRICE TO BOOK VALUE (PBV), DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN PERDAGANGAN ECERAN YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE TAHUN 2010 - 2017 - Marvina, Marvina; Effendi, Maya Syafriana; Sarpan, Sarpan (IKRA-ITH EKONOMIKA, 2020)
This study aims to determine the effect of Current Ratio, Return On Assets, Price To BookValue and Exchange Rates on Stock Prices in Retail Trade companies listed on the Indonesia StockExchange (BEI) period 2010-2017. The data used in this study were obtained from annual publicizedfinancial statements of Retail Trade companies listed on the Indonesia Stock Exchange. After passingthrough the purposive sampling stage, 11 eligible companies are used. The analytical method used inthis research is multiple regression analysis of Fixed Effect model panel data processed with the helpof Eviews 9.0 software.Based on the results of the study note that the CR, ROA, and PBV variables have a positiveand significant effect on the Stock Price, while the Exchange Rate variable does not have a positiveand significant effect on the Stock Price. Of the four variables, the CR variable that has the mostinfluence on stock prices with a coefficient of 451.3749. Adjusted R-Square results in this regressionmodel is equal to 0.924678. These results indicate that the contribution of independent variablesnamely CR, ROA, PBV and Exchange Rate to Share Prices is 92.47% while the remaining 7.53% isexplained by other factors not examined in this model.